Serrated Polyposis Syndrome: A Literature Review - Stephanini, Guilherme Campos; Pinto, Nathan Assis Jordão; Faraco, Jarbas; Correa, Paulo Alberto Falco Pires (Journal of Coloproctology, 2023)
Serrated polyposis syndrome is considered the most prevalent colonic polyposis syndrome in the world. Its importance has been increasingly discussed due to the significant increase in the risk of developing colorectal cancer in its affected individuals, similarly to other well-known polyposis syndromes, such as familial adenomatous polyposis.Serrated lesions of the colon play a major role in this syndrome represented by hyperplastic polyps, serrated sessile lesions and traditional serrated adenomas. Among these lesions, the sessile serrated lesion stands out, considered the main precursor lesion of the serrated pathway of colon carcinogenesis.Diagnosis of serrated polyposis syndrome is given through colonoscopy examination. Diagnostic criteria are: 1) 5 or more serrated lesions proximal to the rectum, all >4mm in size, with at least two >9mm in size; or 2) 20 serrated lesions of any size located anywhere in the large intestine, with >4 lesions proximal to the rectum.The ideal treatment is removal of all relevant serrated lesions by colonoscopy. In case of failure of endoscopic therapy, surgery is indicated. This manuscript is based on two case reports and a literature review and aims to broaden the discussion about the subject.
Keywords: colonoscopy; polyphosis; serrated